2002
DOI: 10.1096/fj.02-0341fje
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological interference with intestinal bile acid transport reduces plasma cholesterol in LDL receptor/apoE deficiency

Abstract: Reduction of plasma cholesterol by statins is fundamental to prevent coronary heart disease. Such therapy is often sub-optimal, however, particularly in patients with reduced LDL receptors (familial hypercholesterolemia), and novel or adjuvant therapies are therefore warranted. Cholesterol elimination is profoundly influenced by the rate of its conversion to bile acids (BA), regulated by the enzyme Cyp7a1. Induced fecal loss of BA by resin treatment reduces plasma cholesterol, presumably through induction of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
17
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 24 publications
5
17
0
Order By: Relevance
“…cholesterol-lowering effects. Our finding supports that of Aoki et al who reported that pitavastatin slightly increases CYP7A1 mRNA levels in guinea pigs 35 and is in agreement with that of Galman et al, 22 who reported that atorvastatin enhances the effect of IBAT inhibition on CYP7A1 mRNA levels in mice lacking both LDL-R and apo E. However, our finding does not agree with those of other authors who have reported no significant effects of lovastatin, 54 pravastatin, 34 simvastatin 35,36 or atorvastatin 30,35 on CYP7A1.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…cholesterol-lowering effects. Our finding supports that of Aoki et al who reported that pitavastatin slightly increases CYP7A1 mRNA levels in guinea pigs 35 and is in agreement with that of Galman et al, 22 who reported that atorvastatin enhances the effect of IBAT inhibition on CYP7A1 mRNA levels in mice lacking both LDL-R and apo E. However, our finding does not agree with those of other authors who have reported no significant effects of lovastatin, 54 pravastatin, 34 simvastatin 35,36 or atorvastatin 30,35 on CYP7A1.…”
Section: Discussionsupporting
confidence: 94%
“…[27][28][29][30][31][32] Lovastatin had an inhibitory effect on CYP7A1 activity in rat liver; 31,33 pravastatin had no significant effect on CYP7A1 activity in human subjects; 34 simvastatin decreased CYP7A1 mRNA levels in guinea pigs, 35 but did not affect 7 -hydroxylation rates in human subjects; 36 atorvastatin decreased CYP7A1 mRNA levels in guinea pigs, 35 showed no significant effects on plasma 7 -hydroxy-4-cholesten-3-one, a validated marker of bile acid synthesis, in FH heterozygotes 30 and enhanced the effects of IBAT inhibition by PR835 on CYP7A1 mRNA and LDL-C levels in mice lacking both LDL-R and apo E. 22 However, the superstatin, pitavastatin, has been shown to slightly increase the level of CYP7A1 mRNA in guinea pigs, 35 but there is still no information available regarding its effects on CYP7A1 in humans.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…[24][25][26] In this study, we found significant increases in fecal bile acid and hepatic SREBP-2 gene expression under YP treatment, but hepatic LDL-R gene expression did not change. To identify changes in expression at the protein level, we performed Western blot analysis for LDL-R (Fig.…”
Section: Gene Expression Analysis In the Livermentioning
confidence: 83%
“…Bile acid-binding resins have been reported to de-repress CYP7A1 activity and to induce hepatic LDL-R expression, resulting in stimulation of plasma LDL clearance, followed by plasma LDL reduction. 26) A slight increase in hepatic CYP7A1 gene expression was observed under YP treatment, but neither mRNA nor protein levels of hepatic LDL-R changed in the SHL-YP group, indicating that the hypolipidemic effect due to YP in C57BL/ 6.KOR-ApoE shl mice did not depend on the capacity for hepatic LDL-R. The increase in fecal bile acid excretion and the large decrease in plasma VLDL cholesterol under YP treatment suggest that acceleration of fecal bile acid excretion is a major mechanism of the hypolipidemic effect induced by YP in C57BL/ 6.KOR-ApoE shl mice.…”
Section: )mentioning
confidence: 99%